Evaluation of Knowledge and Competencies in Sexual and Reproductive Health Care Using an Escape Room with Scenario Simulations - Juan Miguel Martínez-Galiano; Manuel Gonzalez-Cabrera; Julian Rodriguez-Almagro; Antonio Hernández-Martínez (MDPI AG, 2024)
To determine the usefulness of combining two methodologies (OSCE and escape room) in a scenario simulation to evaluate a subject, and determine the evaluation of the students of this experience. An observational cross-sectional study was carried out with students enrolled in a sexual and reproductive health-care course as a part of their nursing degree. The students had to solve four clinical cases based on the contents of the teaching practices of the subject by solving clues that led them to carry out procedures and techniques and provide care in scenario simulators. Students evaluated the experience using the GAMEX (Gameful Experience in Gamification) scale. Mean differences were estimated with their respective 95% confidence intervals. A total of 124 students participated. Of these, 63.7% (79) solved the clinical cases with their knowledge and skills. Most (80.6%, 100) students stated that they completely remembered and applied the knowledge of the topic during the game. Almost all (98.4%, 122) would recommend this experience. The dimensions with the best rating on the GAMEX scale were "fun", with an average score of 4.7 points (0.49), followed by "critical thinking", with 4.2 (0.59). Women presented statistically better scores than men (mean difference: 1.58; 95% CI: 0.55, 2.61). The OSCE combined with an escape room using scenario simulations may be a useful tool to evaluate the subject. In addition, the students were satisfied, had fun, and recommended the experience. This study was not registered.